Perlindungan Hukum Merek Produk Jus Pala di Negeri Morella Kecamatan Leihitu - Nanda Salsabilla Latukau; Teng Berlianty; Muchtar Anshary Hamid Labetubun (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Entrepreneur who has awareness about brand registration is only whose business is big business, but entrepreneur who has micro, small, and medium enterprise  is not aware of it yet.Purposes of the Research: Analyze the form of legal protection for nutmeg juice products as unregistered trademarks, and how to register nutmeg juice products in negeri Morella Kecamatan Leihitu.Methods of the Research: This research is normative legal researches which use legislation approach to slove legal issues in community. Besides, it is also based on community’s norms and statute. This research uses statute approach which uses legislation and conceptual approach.Results of the Research: The results showed that the nutmeg juice product owned by Micro, Small and Medium Enterprises in Morella Country, Leihitu Sub-district had not been able to get legal protection from the state because it had not been registered. The obstacles faced by the nutmeg juice product brand in registering its brand include an error in writing the production address (village name) of nutmeg juice product in the administrative process, the delay in submitting an administrative error correction, and the lack of cooperative members in managing the nutmeg juice brand so that the perpetrators only focuses on improving its products without paying attention to the importance of patenting its own brand.